The Malayonesian Cosmological Doctrines in Some Past Scientific Writings in Malay - Shaharir bin Mohd Zain (Lembaga Penelitian dan Pengabdian Universitas Andalas, 2020)
The Malayonesian cosmological doctrines highlighted here are based on the study of the five Malay inscriptions dated 5th century to 14th century A.D, a traditional Malay folklore on cosmology compiled by Abdullah (1984), and a well known best seller Malay manuscript entitled Taj al-Muluk edited by Syaikh Ismail al-Asyi (1893). We find that the Malayonesian cosmology changes as the people change their religion successively from Hindu to Buddha and to Islam as such that their cosmology became a syncretism of Hindu-Buddha cosmology and Islamic cosmology (after 13th century A.D). But in the second part of the 20th century, the Muslims through out the world began to rediscover their cosmology in relation to a much more pure Islamic cosmology. As a result, a substantial portion of Malayonesians become dualistic or syncretic in their cosmology. Then toward the end of the 20th century came a very powerfull Western cosmology invaded the Muslims thought through economics and malitarism as such that their belief in Islamic cosmology has to accommodate the Western cosmology as well and hence the syncretic Hindu-Buddha-Islamic cosmology became less prominent. A new relativistic dualism, namely a parallel recognition in both the Islamic and the Western cosmologies appeared in Malayonesian cosmology.